2020
DOI: 10.7759/cureus.7279
|View full text |Cite
|
Sign up to set email alerts
|

Horseshoe Kidney Isthmus Infarction After Percutaneous Endovascular Aortic Aneurysm Repair

Abstract: Horseshoe kidneys and their wide-ranging anatomy present a unique test to the open surgical approach for repair of abdominal aortic aneurysms. Endovascular options are currently the desired strategy for treatment of abdominal aortic aneurysms and offer multiple advantages when horseshoe kidneys are present. Even so, the challenging nature of these patients demands a high degree of caution and planning. This case details a patient with horseshoe kidney who underwent percutaneous endovascular aneurysm repair for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…14 In addition, some authors have suggested that an artery supplying a volume of up to 32% of total parenchyma could be occluded in patients with normal renal function 15 In this review, 14.2% (n=7) of the patients had renal infarction, with 1 of them resolving 2 weeks after the EVAR. 16 Dorffner et al 17 reported a patient who had a middle renal artery supplying the parenchymal bridge of the HSK, fully covering the artery with a stent-graft. A renal infarction of the section was diagnosed, but not renal impairment was seen at 6 month follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…14 In addition, some authors have suggested that an artery supplying a volume of up to 32% of total parenchyma could be occluded in patients with normal renal function 15 In this review, 14.2% (n=7) of the patients had renal infarction, with 1 of them resolving 2 weeks after the EVAR. 16 Dorffner et al 17 reported a patient who had a middle renal artery supplying the parenchymal bridge of the HSK, fully covering the artery with a stent-graft. A renal infarction of the section was diagnosed, but not renal impairment was seen at 6 month follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…The most common challenges of aortic surgery and co‐existing HSK include the surgical approach, planning around isthmus and the preservation of blood supply to the kidney (Davidović et al, 2011). Endovascular or open approaches to the aorta are possible (Davidović et al, 2011; Davidovic et al, 2018; Melmer et al, 2020; Bowden & Roche‐Nagle, 2021; Fabiani et al, 2019; Loftus et al, 1998, Kaplan et al, 1999; Ruppert et al, 2004; Frego et al, 2007).…”
Section: Implications For Practicementioning
confidence: 99%